2014
DOI: 10.1080/14789949.2014.985695
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the improving access to psychological therapies for offenders programme at HMP Lincoln: a three year prospective cohort study

Abstract: The mental health needs of prisoners are significant with a high incidence of common mental health problems including anxiety and depression. Extending national initiatives such as the National Health Service Improving Access of Psychological Therapies programme to people in prison offers a valuable opportunity to address these mental health problems and improve continuity of care from prison to the community. This study adopts an observational, prospective cohort design and evaluates an IAPT for offenders ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 18 publications
1
9
0
8
Order By: Relevance
“…Sample sizes ranged from a single‐case study ( n = 1; Mofrad & Webster, 2012) to data from 209 clinical commissioning groups ( n = 537,131; Clark et al ., 2018). One study included only male patients (Adamson, Gibbs, & McLaughlin, 2015), and 17 studies did not report the gender distribution of the patients. Of those studies that reported gender, the average percentage of females was 60.2%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample sizes ranged from a single‐case study ( n = 1; Mofrad & Webster, 2012) to data from 209 clinical commissioning groups ( n = 537,131; Clark et al ., 2018). One study included only male patients (Adamson, Gibbs, & McLaughlin, 2015), and 17 studies did not report the gender distribution of the patients. Of those studies that reported gender, the average percentage of females was 60.2%.…”
Section: Resultsmentioning
confidence: 99%
“…Other target conditions included psychosis, relationship distress, and problematic alcohol use (one study each; 4.9% overall). One study (1.6%) was set in a prison for male offenders (Adamson, Gibbs, & McLaughlin, 2015), whilst two papers (3.3%) studied outcomes with veterans (Clarkson et al ., 2016; Giebel, Clarkson, & Challis, 2014). One study explored the effectiveness of an IAPT for deaf patients (Young et al ., 2017), whilst another explored differences in outcomes based on sexual orientation (Rimes et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mental health in-reach services fall short of community equivalence, with wide variation in service provision and that services for common mental health problems in prison are even more limited [ 9 11 ]. Although the UK government developed the Improving Access to Psychological Therapies (IAPT) for depression and anxiety, these services have been poorly resourced in prisons, with pharmacological interventions often being the only treatment provided [ 12 ]. This is despite some evidence that psychological interventions, even ‘low intensity’ treatments, may be as effective for offenders as they are for the general population [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is despite some evidence that psychological interventions, even ‘low intensity’ treatments, may be as effective for offenders as they are for the general population [ 13 ]. An observational, prospective cohort study evaluating IAPT for prisoners found clinical recovery being achieved in 55% of depression and 52% of anxiety cases [ 12 ]. However, while this is similar to results in community IAPT demonstration sites in Newham and Doncaster [ 14 ] effect sizes in observational studies do not account for regression to the mean.…”
Section: Introductionmentioning
confidence: 99%